Incorporating time‐varying jump intensities in the mean‐variance portfolio decisions. Issue 3 (22nd November 2019) - Zhou, Chunyang; Wu, Chongfeng; Xu, Weidong
Abstract: This paper examines the role of time‐varying jump intensities in forming mean‐variance portfolios. We find that compared with the no‐jump or constant‐jump models, the model which incorporates time‐varying jump intensities better fits the dynamics of the assets returns, and yields mean‐variance portfolios with higher Sharpe ratios. Our research suggests that using a better econometric model that captures non‐normal features in the data has benefits for portfolio allocation even for a mean‐variance investor.